Patient-Specific Blood Flow Analysis for Cerebral Arteriovenous Malformation Based on Digital Subtraction Angiography Images - Zhang, Changwei; Chau, Nixon; Ho, Harvey (Frontiers in Bioengineering and Biotechnology, 2020)
Real-time Digital Subtraction Angiography (DSA) is capable of revealing the cerebral vascular morphology and blood flow perfusion patterns of arterial venous malformations (AVMs). In this study, we analyse the DSA images of a subject-specific left posterior AVM case, and customise a generic electric analog model for cerebral circulation accordingly. The generic model consists of electronic components representing 49 major cerebral arteries and veins, and yields their blood pressure and flow rate profiles. The model was adapted by incorporating the supplying and draining patterns of the AVM to simulate some typical AVM features such as the blood ‘steal’ syndrome, where the flow rate in the left posterior artery increases by almost three times (~300 mL/min vs 100 mL/min) compared with the healthy case. Meanwhile, the flow rate to the right posterior artery is reduced to ~30 mL/min from 100 mL/min despite of the presence of an autoregulation mechanism in the model. In addition, the blood pressure in the draining veins is increased from 9 mmHg to 22 mmHg, and the blood pressure in the feeding arteries is reduced from 85 mmHg to 30 mmHg due to the fistula effects of the AVM. In summary, a first DSA-based AVM model has been developed. More specific-specific AVM cases are required to apply the presented in silico model, and using in vivo data to validate the simulation results.